Evaluation of the Victorian Healthy Homes Program: protocol for a randomised controlled trial. Issue 4 (22nd April 2022) - Campbell, Margaret; Page, Katie; Longden, Thomas; Kenny, Patricia; Hossain, Lutfun; Wilmot, Kerryn; Kelly, Scott; Kim, YoHan; Haywood, Philip; Mulhern, Brendan; Goodall, Stephen; van Gool, Kees; et al.
Abstract : Introduction: The evaluation of the Victorian Healthy Homes Program (VHHP) will generate evidence about the efficacy and cost-effectiveness of home upgrades to improve thermal comfort, reduce energy use and produce health and economic benefits to vulnerable households in Victoria, Australia. Methods and analysis: The VHHP evaluation will use a staggered, parallel group clustered randomised controlled trial to test the home energy intervention in 1000 households. All households will receive the intervention either before (intervention group) or after (control group) winter (defined as 22 June to 21 September). The trial spans three winters with differing numbers of households in each cohort. The primary outcome is the mean difference in indoor average daily temperature between intervention and control households during the winter period. Secondary outcomes include household energy consumption and residential energy efficiency, self-reported respiratory symptoms, health-related quality of life, healthcare utilisation, absences from school/work and self-reported conditions within the home. Linear and logistic regression will be used to analyse the primary and secondary outcomes, controlling for clustering of households by area and the possible confounders of year and timing of intervention, to compare the treatment and control groups over the winter period. Economic evaluation will include a cost-effectiveness and cost-benefit analysis. Ethics and dissemination: Ethical approval was received from Victorian Department of Human Services Human Research Ethics Committee (reference number: 04/17), University of Technology Sydney Human Research Ethics Committee (reference number: ETH18-2273) and Australian Government Department of Veterans Affairs. Study results will be disseminated in a final report and peer-reviewed journals. Trial registration number: ACTRN12618000160235.